A Study on the Adsorption Performance of Heavy Metals and Micropollutants Using Spirulina-based Biochar - 문소은 (The Graduate School, Ajou University, 2024)
Heavy metals (HMs) and micropollutants (MPs) are chemical industry contaminants adversely affecting humans and the environment. These pollutants adsorb on biomass, and among various types of biomass, Spirulina is used to prepare biochar with variations in carbonization temperatures and chemical modification. This process can improve the adsorption performance of pollutants while increasing the additional pore structure and specific surface area of the adsorbent. It was found that Spirulina sp.-based biochar heat-treated at 200°C (SB200) and ZnCl2-modified biochar (ZnSB400) were selected as the suitable adsorbents by comparing adsorption efficiencies according to carbonization temperatures and chemical modification. SB200 exhibited impressive removal efficiencies for bisphenol A (BPA), cadmium (Cd(II)), copper (Cu(II)), and lead (Pb(II)) at 60.59 ± 0.02%, 95.21 ± 0.22%, 96.02 ± 0.10%, and 97.58 ± 0.03%, respectively, primarily due to its abundance of functional groups. Additionally, the highest removal efficiency (for acetaminophen (ACT), 67.68 ± 0.00%; for bisphenol A (BPA), 96.00 ± 0.00%) was exhibited by ZnSB400 with its microporous structure (1.67 nm) and high specific surface area (235.12 m2 g-1). The adsorption kinetic of HMs and MPs on SB200 and ZnSB400 were effectively described by the pseudo-second-order model (R2 > 0.98). The adsorption isotherms were well-fitted using the Redlich-Peterson model (R2 > 0.93). Furthermore, the results of simultaneous adsorption of BPA and HMs on SB200 suggest that there were no significant disparities in the adsorption efficiencies, providing evidence that the pollutants were adsorbed onto distinct sites of the adsorbent without any interference between them. On the other hand, the Brunauer–Emmett–Teller method (BET) and X-ray photoelectron spectroscopy (XPS) results confirmed that the primary mechanisms driving the adsorption of ACT and BPA on ZnSB400 were pore filling and π–π interactions. As a result, Spirulina sp.-based biochar demonstrated its potential as an effective adsorbent for the removal of HMs and MPs from wastewater. The findings of this study highlight the promising applications of this type of biochar in wastewater treatment and environmental remediation efforts.|중금속과 미량오염물질은 화학 공정 등에서 배출되는 오염물질로, 인간과 환경에 부정적인 영향을 미치고 있다. 이러한 오염물질들은 바이오매스에 흡착되는데, 이 연구에서는 다양한 바이오매스 중에서 스피루리나를 사용하였다. 이때 탄화온도와 화학적 개질을 다르게 하여 바이오차를 제조하였다. 이러한 과정은 흡착제의 추가적인 기공구조와 비표면적을 증가시키면서 오염물질에 대한 흡착 성능을 향상시킬 수 있다. 탄화온도와 화학적 개질에 따른 흡착 효율을 비교하여 200oC 스피루리나 바이오차 (SB200)와 ZnCl2 개질 스피루리나 바이오차 (ZnSB400)를 적합한 흡착제로 선정하였다. SB200의 경우, 다른 온도에서 열처리한 바이오차에 비해 작용기가 풍부하여 비스페놀A, 카드뮴, 구리, 그리고 납에 대해 각각 60.59 ± 0.02%, 95.21 ± 0.22%, 96.02 ± 0.10%, 97.58 ± 0.03%로 우수한 제거효율을 보였다. 그리고 ZnSB400은 미세 다공성 구조 (1.67 nm)와 높은 비표면적 (235.12 m2 g-1)으로 아세트아미노펜 (67.68 ± 0.00%) 및 비스페놀 A (96.00 ± 0.00%)에 대한 최대 제거 효율을 나타냈다. 중금속과 미량오염물질에 대한 흡착 동역학의 경우, SB200 및 ZnSB400에서 모두 pseudo-second-model을 통해 잘 설명되었다 (R2 > 0.98). 그리고 흡착 등온식의 경우, Redlich-Peterson 모델이 가장 잘 맞는 모델임을 확인하였다 (R2 > 0.93). 한편, SB200에서 비스페놀 A와 중금속을 동시 흡착한 결과 흡착 효율에 유의미한 차이가 없었고, 이는 오염물질이 서로 간섭 없이 흡착제의 다른 위치에 흡착되었음을 입증하였다. 반면, 비표면적 분석 및 X선 광전자 분광법 결과는 ZnSB400에서 아세트아미노펜 및 비스페놀 A의 흡착의 주요 메커니즘이 기공 충전과 π-π 상호작용임을 나타냈다. 결론적으로, 스피루리나 바이오차는 폐수 중 중금속과 미량오염물질 제거하는데 있어 효과적인 흡착제라고 할 수 있다.
학위논문(석사)--환경공학과,2024. 2
Keywords: Adsorption; Biochar; Heavy metals; Micropollutants; Spirulina